The Impact of Post-COVID-19 Condition on Frontline Healthcare Workers: A Scoping Review - Elsie Duff; Em Pijl; Cindy Fehr; Sai Krishna Gudi (Canadian Journal of Infectious Diseases and Medical Microbiology)
The main goal of this integrative scoping review was to address the knowledge gap and inform policy and research regarding the impact of post-COVID-19 conditions on frontline healthcare workers (HCWs). An integrative scoping review using Arksey and O’Malley’s framework examined post-COVID-19 conditions in frontline HCWs. We searched CINAHL, EMBASE, APA PsycINFO, PubMed, Social Science Database, ProQuest, Social Science Journals, and Web of Science, including dissertations, conference proceedings, and government publications for gray literature. A preestablished data extraction tool was developed to capture relevant information about post-COVID-19 conditions in HCWs. Of the total 42 studies, the majority were cross-sectional in design (29) and conducted mainly in countries such as Italy (4), India (3), and Brazil (3). Study findings reveal that a substantial proportion of HCWs in various countries were diagnosed with post-COVID-19 condition, which included persistent symptoms affecting physical and mental well-being. Persistent symptoms, particularly fatigue and anxiety, were associated with a poorer quality of life, decreased work ability, and impaired health-related quality of life among HCWs. Fatigue was a frequently reported symptom in many studies, often accompanied by weakness, muscle pain, shortness of breath, anxiety, depression, and sleep disturbances. The evidence generated through this research examining post-COVID-19 conditions among HCWs is a foundation for informing policy in the healthcare workforce. These findings also address the gap in research on the broader impacts of the COVID-19 pandemic on employers and the healthcare workforce.